EFISIENSI PENGGUNAAN FAKTOR PRODUKSI USAHATANI CABE DI KELURAHAN MARAWAS KECAMATAN TONDANO UTARA KABUPATEN MINAHASA - Juliana Ruth Mandei (Sam Ratulangi University, 2011)
The purpose of this research is to know the efficiency of factors production utilization of the chili farm in Marawas Village Subdistict North Tondano Regency of Minahasa. The research has been carried out for 3 months from Mei 2011 to July 2011. The location was selected by purposive sampling because almost of the Marawas village citizen depend on chili farm, with the number of respond is 40 farmer. Data were analyzed quantitively utilizing statistical calculation of regression analysis. Primary data obtained are the amount of production, the wide of land, the amount of labor, seed, organic and NPK fertilizer, pesticide dan the growth incentive substance (ZPT). The result of research showed that the regression model suitable to be researched. From the F-test showed the utilization of the wide of land, the amount of labor, seed, organic and NPK fertilizer, pesticide dan the growth incentive substance (ZPT) have an significant influence toward the amount of production, however, T-test found that the production factors wide of land, the amount of labor and organic fertilizer as separated have an significant influence toward the amount of production. The production’s factors the amount of seed, NPK fertilizer dan the growth incentive substance (ZPT) haven’t influence toward the amount of production. The utilization of the factors of production the wide of land, the amount of labor, seed, organic and NPK fertilizer dan the growth incentive substance (ZPT) of the chili farm in Marawas Village were technically efficient but not economically efficient, whereas the utilization of pesticide was not technically and economically efficient. Therefor it is suggested to chili farmer of the Marawas Village Subdistict North Tondano Regency of Minahasa to reduced over pesticide utilization to extermination of chili’s pest and desease with other way, which more environment and not contained chemical material, for example manually, mechanical and physical controlling.